2002
DOI: 10.1556/aalim.31.2002.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Stability and stabilization of the anthocyanins fromEuterpe oleraceamart

Abstract: The effect of light on the stability and stabilization of the anthocyanins isolated from freeze-dried aqueous extracts of fruits of Euterpe oleracea were studied, using crude and purified extracts at pH 2.2 and 3.0. Crude extract was 80.0 times more stable than the purified one at pH 2.2 and 24.3 at pH 3.0. Stabilization with tannic acid was attempted and resulted in 65% half-life increase of the anthocyanins of the crude and a considerable half-life increase (610%) of the purified one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 7 publications
2
10
1
3
Order By: Relevance
“…The authors observe that the samples used in the present study had natural pH, while in the literature the pH of the samples was artificially diminished to around 3.5, as expected, hence reducing the anthocyanins decay (BOBBIO; BOBBIO;FADELLI, 2002;PACHECO-PALENCIA;HAWKEN;TALCOTT, 2007).…”
Section: Kinetic Calculationssupporting
confidence: 73%
See 1 more Smart Citation
“…The authors observe that the samples used in the present study had natural pH, while in the literature the pH of the samples was artificially diminished to around 3.5, as expected, hence reducing the anthocyanins decay (BOBBIO; BOBBIO;FADELLI, 2002;PACHECO-PALENCIA;HAWKEN;TALCOTT, 2007).…”
Section: Kinetic Calculationssupporting
confidence: 73%
“…De Rosso and Mercadante (2007) obtained t 1/2 = 909 hours in a commercial drink with pH 2.5 (at 20 °C), and Bobbio, Bobbio and Fadelli (2002), using a non-pasteurized drink, found t 1/2 = 301.2 hours for drinks with pH 2.2 and t 1/2 = 182.4 hours at pH 3.0. of cyanidin-3-glucoside 449.2 g.mol -1 ; DF is the dilution factor; ε is the molar absorptivity of cyanidin-3-glucoside 26,900.…”
Section: The Temperature and Time Effect On The Anthocyanin Contentmentioning
confidence: 97%
“…Previous reports on the anthocyanin composition of açai fruit have been limited. A previous study determined cyanidin-3-glucoside and cyanidin-3-rutinoside as the major anthocyanins in açai (Lichtenthäler et al, 2005), while others found that cyanidin-3-arabinoside and cyanidin-3-arabinosylarabinoside were the most abundant (Bobbio, Bobbio, Oliveira, & Fadelli, 2002). However, both cyanidin-3-arabinoside and cyanidin-3-arabinosylarabinoside were not detectable in AEA under our experimental conditions.…”
Section: Hplc-ms/ms Detection Of Anthocyanins In Aeacontrasting
confidence: 56%
“…), an Amazonian palm, is of economic importance due to the production of energy drinks, which are produced from its fruit (Rogez 2000;Bobbio et al 2002). The fruits contain high amounts of lipids and minerals, such as K, Ca, and Mg (Menezes et al 2008;Yuyama et al 2011).…”
Section: Introductionmentioning
confidence: 99%